A novel distance protection scheme for HVDC lines based on R-L model. (September 2018) - Qin, Yu; Wen, Minghao; Zheng, Junchao; Bai, Yu
Highlights: A novel single-end distance protection scheme for HVDC lines is proposed. This protection is based on the linear distribution of low frequency voltage signals along the line. Principles of mho relay are improved and applied in the new protection. An internal fault can be detected if the measure voltage is opposite in sign with the compensating voltage. Compared with other single-end HVDC line protections, this novel method has numerous merits. Abstract: HVDC transmission system is becoming increasingly desirable for its obvious technical and environmental advantages. A novel single-end distance protection scheme for HVDC lines is proposed in this paper. It is based on the linear distribution of low frequency voltage signals between the relay point and setting point. An internal fault can be detected if the low-pass filtered measure voltage is opposite in sign with the compensating voltage at the setting point, which can be calculated with the R-L differential-equation algorithm. To find a tradeoff between operating speed and accuracy, the protection is divided into K zones, each of which has different protection scopes and cut-off frequencies. A two-terminal HVDC system and a multi-infeed HVDC system are respectively built in EMTDC. Comprehensive simulation results have indicated that the proposed protection scheme has satisfactory operation performance and will be not influenced by system topologies or parameters. Besides, it is not sensitive to noises or voltage levels. Compared with many other single-end protections for HVDC lines, this novel distance protection has clear setting principles, lower sampling frequency, smaller calculation amount and faster operating speed.